Silicon-carbon negative electrode material and preparation method and application thereof
The liquid phase in-situ polymerization coats the surface of the silicon-carbon composite to form a dense carbon layer, which solves the structural rupture problem of silicon-carbon composite materials due to volume expansion in lithium-ion batteries, improves the cycling performance and safety of the battery, and reduces production costs.
Patent Information
- Application Number
- CN202510716654.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-30
- Publication Date
- 2025-08-29
AI Technical Summary
The existing silicon-carbon composite materials are structurally ruptured and the SEI film is repeatedly generated due to volume expansion in lithium-ion batteries, which affects the battery life and safety performance. The existing coating methods have problems such as difficult to control the thickness and uniformity of the carbon layer and high energy consumption.
Using the liquid phase in-situ polymerization coating method, a dense carbon layer is formed on the surface of the silicon-carbon composite precursor through hydrothermal reaction, including a mixed silicon-carbon composite precursor with a solvent and an organic carbon source, hydrothermal reaction and heat treatment are carried out to form a continuous carbon cladding layer.
It improves the electrochemical stability and mechanical strength of the material, inhibits side reactions, enhances structural stability, reduces the risk of powdering, improves circulation performance and safety, and has a simple process and low cost.
Smart Images

Figure CN120553680A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium-ion battery materials, and in particular to a silicon-carbon negative electrode material, a preparation method and an application thereof, and in particular to a silicon-carbon negative electrode material based on liquid phase in-situ polymerization coating, a preparation method and an application thereof. Background Art
[0002] With the rapid development of new energy vehicles and high-energy-density energy storage systems, lithium-ion batteries are placing higher demands on anode materials with high specific capacity and high stability. Silicon-carbon composites are widely considered to be important candidates for next-generation lithium battery anode materials due to their excellent theoretical specific capacity and good cycling performance. However, silicon undergoes a volume expansion of over 300% during the lithium insertion / delithiation process, which can easily cause material structure fracture, electrode pulverization, and repeated formation of solid electrolyte interface films (SEI films), seriously affecting battery life and safety performance.
[0003] To alleviate the above problems, the industry usually adopts a carbon coating strategy to construct a buffer and protective layer on the surface of silicon-carbon materials, thereby improving their conductivity, structural stability and inhibiting interfacial side reactions. The current mainstream coating methods include gas phase coating and solid phase coating: the gas phase coating process decomposes the carbon source gas (such as acetylene, ethylene, methane, propylene, etc.) at high temperature to deposit a uniform carbon layer on the silicon-carbon surface, which can significantly improve the conductivity and mechanical strength of the material. However, this method has low gas utilization, high energy consumption, and it is difficult to accurately control the thickness and uniformity of the carbon layer. Solid phase coating often uses tar or asphalt as the carbon source, but due to its poor dispersibility and film formation uniformity, it is often difficult to form a dense and continuous carbon layer, and it is easy to have particle agglomeration or carbon source coking alone.
[0004] Therefore, developing a coating method with simple process, high carbon source utilization and excellent coating uniformity is a key breakthrough point in the current industrial development of silicon-carbon negative electrodes. Summary of the Invention
[0005] The purpose of the present invention is to address the defects of the prior art and propose a silicon-carbon negative electrode material based on liquid phase in-situ polymerization coating, a preparation method and an application.
[0006] To achieve the above objectives, in a first aspect, an embodiment of the present invention provides a method for preparing a silicon-carbon negative electrode material based on liquid phase in-situ polymerization coating, the preparation method comprising:
[0007] Step S1, weighing a silicon-carbon composite precursor or preparing a silicon-carbon composite precursor;
[0008] Step S2, mixing the silicon-carbon composite precursor and a solvent in a certain mass ratio, stirring evenly, to form a solvent system;
[0009] Step S3, adding an organic carbon source to the solvent system and stirring uniformly to form an organic precursor solution;
[0010] Step S4, subjecting the organic precursor solution to a hydrothermal reaction, causing the organic carbon source to undergo an in-situ polymerization reaction on the surface of the silicon-carbon composite precursor to form a dense coating layer, thereby obtaining an intermediate product;
[0011] Step S5: heat-treating the intermediate product, sieving the discharged product, and obtaining a silicon-carbon negative electrode material coated by liquid phase in-situ polymerization.
[0012] Preferably, the preparation of the silicon-carbon composite precursor specifically includes: placing a porous carbon substrate in a deposition device, heating the substrate to 500°C to 700°C at a heating rate of 1°C / min to 5°C / min under a protective atmosphere, introducing a silicon source gas, and maintaining the temperature for 1 hour to 5 hours, so that the silicon element decomposed by the silicon source gas is deposited in the pores and on the surface of the porous carbon substrate and grows into a nano-silicon material, thereby obtaining a silicon-carbon composite precursor;
[0013] The porous carbon matrix comprises: one or more of resin carbon, biomass carbon, pitch coke or petroleum coke;
[0014] The silicon source gas includes one or more of monosilane, disilane, dichlorosilane, trichlorosilane, tetrachlorosilane, and hexachlorodisilane; the flow rate of the silicon source gas is 1 L / min to 100 L / min;
[0015] The protective gas of the protective atmosphere includes: nitrogen and / or argon; the flow rate of the protective gas is 1L / min to 50L / min;
[0016] The specific surface area of the silicon-carbon composite precursor is 60 m 2 / g~200m 2 / g, and the carbon content in the silicon-carbon composite precursor is 40wt% to 55wt%.
[0017] Preferably, the solvent includes: deionized water or an organic solvent; the organic solvent includes: one or more of molecular alcohol solvents, ether solvents, amine solvents, and ester solvents;
[0018] The mass ratio of the silicon-carbon composite precursor to the solvent is 0.3:10 to 3:10;
[0019] The organic carbon source includes one or more of aromatic organic compounds, small molecule sugar organic compounds, polysaccharide organic compounds, organic acid organic compounds, and amide organic compounds;
[0020] The mass ratio of the organic carbon source to the silicon-carbon composite precursor is 0.5:1 to 3:1.
[0021] More preferably, the organic solvent specifically includes: one or more of ethylene glycol, isopropyl alcohol, polyethylene glycol, dimethyl ether, ethanolamine, methylethanolamine, methyl propionate, γ-butyrolactone, and tetrahydrofuran;
[0022] The organic carbon source specifically includes: one or more of phenol, hydroquinone, catechol, starch, cyclodextrin, glucose, tannic acid, tartaric acid, and urea.
[0023] Preferably, the step S4 specifically includes: placing the organic precursor solution in a hydrothermal reactor, continuing to stir, heating to 25°C to 300°C under a pressure of 2Mpa to 3Mpa for a hydrothermal reaction, and keeping the temperature for 5 hours to 12 hours, so that the organic carbon source undergoes an in-situ polymerization reaction on the surface of the silicon-carbon composite precursor to form a dense coating layer to obtain an intermediate product.
[0024] Preferably, the step S5 specifically includes: placing the intermediate product in a high-temperature device, heating it to 400°C to 800°C in an inert gas environment for heat treatment for 2 hours to 5 hours, cooling it to room temperature, discharging it, and sieving it to obtain a silicon-carbon negative electrode material based on liquid phase in-situ polymerization coating.
[0025] In a second aspect, an embodiment of the present invention provides a silicon-carbon negative electrode material based on liquid phase in-situ polymerization coating prepared by the preparation method described in the first aspect, wherein the silicon-carbon negative electrode material comprises: a silicon-carbon composite precursor, a coating layer coated on the outer surface of the silicon-carbon composite precursor;
[0026] The silicon-carbon composite precursor comprises: a porous carbon matrix, and nano-silicon materials deposited and grown in the pores and on the surface of the porous carbon matrix;
[0027] The coating layer is a continuous film-like carbon coating layer formed by closely arranged carbon particles.
[0028] Preferably, the specific surface area of the silicon-carbon composite precursor is 60 m 2 / g~200m 2 / g, the carbon content in the silicon-carbon composite precursor is 40wt% to 55wt%;
[0029] The Dv50 of the silicon-carbon negative electrode material is between 5 μm and 10 μm; the carbon content of the silicon-carbon negative electrode material is between 40 wt% and 60 wt%; the specific surface area of the silicon-carbon negative electrode material is less than 2.5 m 2 / g.
[0030] In a third aspect, an embodiment of the present invention provides a negative electrode plate, which includes a silicon-carbon negative electrode material coated based on liquid phase in situ polymerization prepared by the preparation method described in the first aspect, or a silicon-carbon negative electrode material coated based on liquid phase in situ polymerization described in the second aspect.
[0031] In a fourth aspect, an embodiment of the present invention provides a lithium-ion battery, comprising the negative electrode sheet described in the third aspect.
[0032] The embodiments of the present invention provide a silicon-carbon negative electrode material based on liquid phase in-situ polymerization coating, a preparation method, and an application thereof, which have the following technical effects compared to the prior art:
[0033] (1) The preparation method of the silicon-carbon negative electrode material based on liquid-phase in-situ polymerization coating provided in an embodiment of the present invention comprises the following steps: mixing a silicon-carbon composite precursor and a solvent in a certain mass ratio, stirring evenly, and forming a solvent system; adding an organic carbon source to the solvent system, stirring evenly, and forming an organic precursor solution; subjecting the organic precursor solution to a hydrothermal reaction, so that the organic carbon source undergoes an in-situ polymerization reaction on the surface of the silicon-carbon composite precursor to form a dense coating layer, and obtaining an intermediate product; subjecting the intermediate product to a heat treatment, and sieving the discharged product to obtain a silicon-carbon negative electrode material based on liquid-phase in-situ polymerization coating.
[0034] Compared with the gas phase carbon coating process, the advantages of the liquid phase in-situ polymerization coating process provided by the present invention include:
[0035] ① Inhibit side reactions and improve safety: This method uses liquid-phase in-situ polymerization to form a uniform and dense carbon layer on the surface of the silicon-carbon negative electrode, effectively isolating the electrolyte from direct contact with active silicon, thereby inhibiting side reactions and gas generation and improving battery safety.
[0036] ② Enhance structural stability and improve cycle: The silicon-carbon negative electrode material treated with hydrothermal coating exhibits better mechanical strength under high-pressure environment, reduces the risk of pulverization, and improves cycle stability.
[0037] ③ The process is simple and low-cost: Compared with gas phase or solid phase methods, this process can complete the coating at a lower temperature, has a high carbon source utilization rate, and the solvent is recyclable, avoiding expensive equipment investment and high energy consumption problems, and has good prospects for industrial application.
[0038] (2) The preparation method provided by the embodiment of the present invention takes hydrothermal reaction as the core, uniformly disperses the organic carbon source on the surface of the silicon-carbon composite precursor through a solvent medium, and undergoes intermolecular condensation, dehydration and decarboxylation reactions during the hydrothermal process to form an intermediate product and derive into a polymer, ultimately forming a porous carbon precursor with a broad aromatic network structure, which is then carbonized. Since the in-situ polymerization occurs on the surface of the precursor particles, the bond with the precursor interface is stronger, avoiding the non-selective site deposition of the gaseous carbon source in the gas phase coating. Therefore, the liquid phase in-situ polymerization coating can form a continuous and dense carbon layer on the surface of the silicon-carbon precursor, thereby effectively improving the electrochemical stability of the silicon-carbon negative electrode material.
[0039] (3) When the silicon-carbon composite negative electrode material prepared by the present invention is used in lithium batteries, it can effectively alleviate the volume expansion of silicon, improve the cycle performance and charge and discharge capacity of the lithium-ion battery, and improve the pressure resistance of the sample. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 Flowchart of the preparation method of the silicon-carbon negative electrode material provided in an embodiment of the present invention.
[0041] Figure 2 a is a scanning electron microscope (SEM) image of the silicon-carbon composite precursor provided in Example 1 of the present invention.
[0042] Figure 2 b is an SEM image of the silicon-carbon negative electrode material prepared in Example 1 of the present invention.
[0043] Figure 3 This is the X-ray diffraction (XRD) pattern of the silicon-carbon negative electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0044] To make the objectives, technical solutions, and advantages of the present invention more apparent, the present invention will be further described in detail below with reference to the accompanying drawings. It is apparent that the embodiments described are only some, not all, of the present invention. All other embodiments derived by persons of ordinary skill in the art based on the embodiments of the present invention without creative effort are intended to fall within the scope of protection of the present invention.
[0045] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments.
[0046] The embodiment of the present invention provides a method for preparing a silicon-carbon negative electrode material based on liquid phase in-situ polymerization coating, such as Figure 1 As shown, the specific steps include:
[0047] Step S1, weighing a silicon-carbon composite precursor or preparing a silicon-carbon composite precursor;
[0048] The present invention can directly weigh the silicon-carbon composite precursor sold on the market, or can prepare the silicon-carbon composite precursor; the specific surface area of the silicon-carbon composite precursor weighed or prepared in the embodiment of the present invention is 60m 2 / g~200m 2 / g, the carbon content in the silicon-carbon composite precursor is 40wt% to 55wt%, and the range of the particle size Dv50 of the silicon-carbon composite precursor does not need to be specifically limited and can be selected according to needs, for example, it can be between 5μm and 9μm;
[0049] The specific process for preparing the silicon-carbon composite precursor is as follows: placing a porous carbon substrate in a deposition device, heating it to 500°C to 700°C at a heating rate of 1°C / min to 5°C / min under a protective atmosphere, introducing a silicon source gas, and keeping the temperature for 1 to 5 hours, so that the silicon element decomposed by the silicon source gas is deposited in the pores and on the surface of the porous carbon substrate and grows into a nano-silicon material, thereby obtaining a silicon-carbon composite precursor;
[0050] The porous carbon matrix includes one or more of resin carbon, biomass carbon, pitch coke or petroleum coke;
[0051] The silicon source gas includes one or more of monosilane, disilane, dichlorosilane, trichlorosilane, tetrachlorosilane, and hexachlorodisilane; the flow rate of the silicon source gas is 1 L / min to 100 L / min;
[0052] The protective gas of the protective atmosphere includes: nitrogen and / or argon; the flow rate of the protective gas is 1L / min to 50L / min;
[0053] Step S2, mixing the silicon-carbon composite precursor and the solvent in a certain mass ratio, stirring evenly, to form a solvent system;
[0054] In this step, the silicon-carbon composite precursor and the solvent are sequentially added into the hydrothermal reactor in a certain mass ratio, and stirred and mixed uniformly in the hydrothermal reactor. The mass ratio of the silicon-carbon composite precursor to the solvent is 0.3:10 to 3:10.
[0055] The solvent includes: deionized water or an organic solvent; the organic solvent includes: one or more of molecular alcohol solvents, ether solvents, amine solvents, and ester solvents; the organic solvent specifically includes: one or more of ethylene glycol, isopropyl alcohol, polyethylene glycol, dimethyl ether, ethanolamine, methylethanolamine, methyl propionate, γ-butyrolactone, and tetrahydrofuran.
[0056] Step S3, adding an organic carbon source to the solvent system and stirring uniformly to form an organic precursor solution;
[0057] Among them, the mass ratio of the organic carbon source to the silicon-carbon composite precursor is 0.5:1 to 3:1, and can be a ratio within this range, for example: 0.5:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, etc., but is not limited to the listed ratios, and other unlisted ratios within the ratio range are also applicable; when the mass ratio of the organic carbon source to the silicon-carbon composite precursor is less than 0.5:1, the amount of organic carbon source used is too low, which will result in a higher specific surface area of the coated material; when the amount of organic carbon source used is too high, it will cause the sample particle size to grow larger and the coating layer to be thicker, which will affect the ion deintercalation path on the one hand and is not conducive to ion transport, and on the other hand will reduce the proportion of active silicon, resulting in a decrease in the overall specific capacity.
[0058] The organic carbon source includes: one or more of aromatic organic compounds, small molecule sugar organic compounds, polysaccharide organic compounds, organic acid organic compounds, and amide organic compounds; the organic carbon source specifically includes: one or more of phenol, hydroquinone, catechol, starch, cyclodextrin, glucose, tannic acid, tartaric acid, and urea.
[0059] Step S4, subjecting the organic precursor solution to a hydrothermal reaction, causing the organic carbon source to undergo an in-situ polymerization reaction on the surface of the silicon-carbon composite precursor to form a dense coating layer, thereby obtaining an intermediate product;
[0060] Specifically, the organic precursor solution is placed in a hydrothermal reactor and continuously stirred. The temperature is raised to 25°C to 300°C under a pressure of 2Mpa to 3Mpa for a hydrothermal reaction. The heat preservation time is 5 hours to 12 hours, so that the organic carbon source undergoes an in-situ polymerization reaction on the surface of the silicon-carbon composite precursor to form a dense coating layer to obtain an intermediate product.
[0061] The temperature of the hydrothermal reaction in this step is 25°C to 300°C, and can be any temperature within this range, for example, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, etc., but is not limited to the listed temperatures, and other temperatures not listed within this temperature range are equally applicable. When the hydrothermal reaction temperature is too low, the carbon source monomers polymerize on the material surface, undergo intermolecular condensation, undergo dehydration and decarboxylation reactions, and undergo aromatization to a limited extent, hindering the formation of a dense coating layer. When the temperature is too high, the oxygen atoms contained in the carbon source further oxidize the active silicon, resulting in a loss of negative electrode capacity.
[0062] Step S5, heat-treating the intermediate product, sieving the discharged product, and obtaining a silicon-carbon negative electrode material coated by liquid phase in-situ polymerization;
[0063] Specifically, the intermediate product is placed in a high-temperature device and heated to 400°C to 800°C under an inert gas atmosphere for a heat treatment period of 2 to 5 hours. The product is then cooled to room temperature, discharged, and sieved to obtain a silicon-carbon anode material coated by liquid-phase in-situ polymerization. The high-temperature device includes, but is not limited to, a tubular furnace. A 300-mesh sieve can be used for screening in this step to prevent possible agglomeration during the heat treatment process.
[0064] When the particle size Dv50 of the silicon-carbon composite precursor is between 5 μm and 9 μm, the Dv50 of the silicon-carbon negative electrode material finally prepared is about 5 μm to 10 μm, the carbon content of the silicon-carbon negative electrode material is between 40 wt% and 60 wt%, and the specific surface area is less than 2.5 m 2 / g.
[0065] The present invention uniformly disperses the organic carbon source on the surface of the silicon-carbon composite precursor through a solvent medium, and undergoes intermolecular condensation, dehydration, and decarboxylation reactions during the hydrothermal process to form an intermediate product that is derived into a polymer, ultimately forming a porous carbon precursor with a broad aromatic network structure, which is then carbonized. Since in-situ polymerization occurs on the surface of the precursor particles, it is more strongly bonded to the precursor interface, avoiding the non-selective site deposition of the gaseous carbon source in the gas phase coating. Therefore, the liquid phase in-situ polymerization coating can form a continuous and dense carbon layer on the surface of the silicon-carbon precursor, thereby effectively improving the electrochemical stability of the silicon-carbon negative electrode material.
[0066] The silicon-carbon negative electrode material based on liquid phase in-situ polymerization coating prepared by the above preparation method provided in an embodiment of the present invention comprises: a silicon-carbon composite precursor, and a coating layer coated on the outer surface of the silicon-carbon composite precursor; wherein the silicon-carbon composite precursor comprises: a porous carbon matrix, and nano-silicon materials deposited and grown in the pores and on the surface of the porous carbon matrix, and the specific surface area of the silicon-carbon composite precursor is 60m 2 / g~200m 2 / g, the carbon content in the silicon-carbon composite precursor is 40wt% to 55wt%. The coating layer is a continuous film-like carbon coating layer structure formed by closely arranged carbon particles.
[0067] The specific surface area test of the silicon-carbon composite precursor and the finished silicon-carbon negative electrode material of the present invention is conducted using a specific surface area analyzer (model: Micromeritics ASAP2460): the sample to be tested is first sieved using a 200-mesh sieve; then, a degassing treatment is performed, usually by placing the sample in a vacuum and heating and degassing it at a high temperature of 200°C for several hours (6 hours). Then, in a constant low temperature environment (-196°C), nitrogen is introduced, the nitrogen pressure is controlled, and the sample is adsorbed and desorbed at different pressures to obtain the isothermal adsorption-desorption curve of the sample; then, based on the isothermal adsorption-desorption curve, the specific surface area of the sample is calculated using BET fitting.
[0068] The carbon content testing method of the present invention uses a carbon-sulfur analyzer (model: CS-2800) to test the carbon content of a material. The testing principle is to oxidize the carbon in the sample into gases such as CO and CO2 under high temperature, and then use infrared spectroscopy to detect and analyze the gases to calculate the carbon and sulfur content in the sample. In addition, samples with a carbon content of not less than 6% and samples with a carbon content of less than 6% are defined as high-carbon samples and low-carbon samples, respectively. The test requires taking samples of different masses. The high-carbon sample and the low-carbon sample are sampled in 50mg and 100mg portions, respectively. 2.5g and 2.1g of a special rare earth co-solvent are added to the samples, respectively. The samples are placed in a crucible and placed in the carbon-sulfur analyzer for testing, and the carbon content test data is read out.
[0069] In the present invention, particle size Dv50 refers to the volume median particle size of the material, indicating the particle size corresponding to 50% of the volume distribution of the material, which is a well-known meaning in the art. The particle size Dv50 of the material in the present invention can be measured using instruments and conventional methods known in the art. Specifically, 1g of silicon-carbon anode material is weighed and added to 20ml of deionized water, followed by the addition of 50ul of a 1% aqueous solution of ethylphenyl polyethylene glycol dispersant, followed by ultrasonication for 5 minutes. The dispersion is then added to a Mastersizer 3000 laser particle size analyzer from Malvern Instruments Co., Ltd. for particle size measurement, and the Dv50 value is then read.
[0070] The silicon-carbon negative electrode material coated based on liquid phase in-situ polymerization in the embodiment of the present invention can be used as a negative electrode active material to prepare a negative electrode plate.
[0071] The preparation method for the negative electrode sheet is conventional and known. Specifically, the preparation method comprises: uniformly mixing the aforementioned silicon-carbon negative electrode material coated by liquid-phase in-situ polymerization, other additive materials, and a solvent in appropriate proportions to form a slurry; then, coating the slurry on both sides of a current collector; and drying to obtain the negative electrode sheet. The other additive materials include conductive materials and binders. The conductive materials include one or more of graphite conductive agents, conductive carbon black, and graphene; graphite conductive agents include one or more of KS-6, KS-15, SFG-6, and SFG-15; and conductive carbon black includes one or more of acetylene black, Super P, Super S, 350G, carbon fiber (VGCF), carbon nanotubes (CNTs), Ketjen black, and activated carbon. The binder includes one or more of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, carboxymethyl cellulose, sodium carboxymethyl cellulose, polymethyl methacrylate, polyacrylic acid, polyacrylonitrile, styrene-butadiene rubber, polyvinyl alcohol, polytetrafluoroethylene, polyacrylamide, polyvinyl acetate, or polyurethane. The solvent used in the process of preparing the negative electrode sheet includes one or more of deionized water, ethanol, acetone, or diacetyl. The current collector includes but is not limited to copper foil.
[0072] The negative electrode plate provided by the embodiment of the present invention, which contains a silicon-carbon negative electrode material coated based on liquid phase in situ polymerization, can be assembled with an electrolyte / solid electrolyte, a separator and a positive electrode plate into a lithium-ion battery. The lithium-ion battery includes a liquid lithium-ion battery, an all-solid lithium battery or a semi-solid lithium battery.
[0073] In order to better understand the technical solution provided by the present invention, the preparation process and characteristics of the silicon-carbon negative electrode material based on liquid phase in-situ polymerization coating of the present invention are respectively illustrated by multiple specific examples below.
[0074] Example 1
[0075] This embodiment provides a preparation process of a silicon-carbon negative electrode material coated by liquid phase in-situ polymerization, which is detailed as follows.
[0076] (1) Weigh 100 g of silicon-carbon composite precursor; use a surface area analyzer (model: Micromeritics ASAP2460) to test the specific surface area of the silicon-carbon composite precursor, which is 102.3 m 2 / g; the carbon content of the silicon-carbon composite precursor was tested by a carbon-sulfur analyzer (model: Gangyannake CS-2800) and was 45.1%.
[0077] (2) The silicon-carbon composite precursor and deionized water were sequentially added into a hydrothermal reactor at a mass ratio of 0.5:10, and stirred to form a solvent system.
[0078] (3) Adding starch as an organic carbon source to the solvent system, continuing to stir in a hydrothermal reactor, and mixing uniformly to form an organic precursor solution, wherein the mass ratio of starch to silicon-carbon composite precursor is 0.5:1.
[0079] (4) The hydrothermal reactor is heated to 240°C under a pressure of 2 MPa and kept warm for 5 hours. The organic precursor solution undergoes a hydrothermal reaction, causing the organic carbon source to undergo an in-situ polymerization reaction on the surface of the silicon-carbon composite precursor to form a dense coating layer. After the insulation is completed, the temperature of the hydrothermal reactor is lowered to room temperature. The material is discharged, filtered, and vacuum-dried to obtain an intermediate product.
[0080] (5) The intermediate product was transferred to a porcelain boat and placed in a tube furnace. Under a nitrogen atmosphere, the temperature was raised to 500°C at a heating rate of 2°C / min and kept at this temperature for 2 hours for heat treatment. After discharge, the material was sieved through a 300-mesh sieve to obtain a silicon-carbon negative electrode material with uniform particle size distribution based on liquid phase in situ polymerization coating.
[0081] The SEM image of the silicon-carbon composite precursor used in step (1) of this embodiment is as follows: Figure 2 As shown in a.
[0082] This is the SEM image of the silicon-carbon negative electrode material prepared in Example 1 of the present invention, as shown in FIG. Figure 2 As shown in b, it can be observed Figure 2 b The surface of the material particles after liquid phase in-situ polymerization coating is relatively smooth and dense. Figure 2 The surface morphology of a silicon-carbon composite precursor shows no obvious particle agglomeration or carbon layer cross-section phenomenon, indicating that the carbon coating layer formed by liquid phase in situ polymerization is tightly bonded to the surface of the carbon composite precursor, forming a continuous and dense carbon layer structure.
[0083] Figure 3 The XRD pattern of the silicon-carbon negative electrode material prepared in Example 1 of the present invention is as follows: Figure 3 As shown, the horizontal axis is the diffraction angle 2θ (unit °, degree), and the vertical axis is the intensity (Intensity, unit au) through Figure 3 It can be seen that at diffraction angles 2θ of 28.4°, 47.3°, and 56.1°, broad diffraction peaks associated with amorphous silicon are observed, while no obvious diffraction peaks of silicon oxide are observed, indicating that the material remains amorphous after hydrothermal reaction and heat treatment. This structure helps to alleviate the volume expansion of silicon-carbon negative electrode material particles and maintain the stability of the material structure, thereby improving the cycle life and safety performance of the material during the charge and discharge process.
[0084] The specific surface area of the silicon-carbon negative electrode material prepared in this embodiment was tested using a specific surface area analyzer (model: Micromeritics ASAP2460). The test data are detailed in Table 1.
[0085] The silicon-carbon negative electrode material prepared in this embodiment was used to prepare pole pieces and assembled into button-type half-cells for testing. The specific process is as follows.
[0086] Preparation of the electrode: silicon-carbon negative electrode material, conductive agent Super P, and binder polyvinylidene fluoride are weighed in a mass ratio of 8:1:1, and then added to an appropriate amount of deionized water. The slurry is prepared using a beater, and the slurry is coated on the copper foil current collector. The electrode is baked in a vacuum oven at 80°C for 12 hours, and then the dried electrode is cut into discs with a diameter of 14 mm to obtain the electrode. The electrode is transferred to a glove box filled with argon for standby use.
[0087] Button half-cell assembly process: In an argon-filled glove box, the prepared electrode and lithium sheet are assembled into a button half-cell by conventional methods, wherein the electrolyte used in the assembled battery is lithium hexafluorophosphate (LiPF6) with a molar concentration of 1 mol / L, and the solvent of the electrolyte is ethylene carbonate (EC), dimethyl carbonate (DMC) and diethyl carbonate (DEC), and the volume ratio of EC, DMC and DEC is 1:1:1; the diaphragm uses a polyethylene diaphragm.
[0088] Coin-type half-cell testing process: The assembled coin-type half-cells were electrochemically tested using a BlueDian battery testing system, with a voltage window set to 0.01V–2V and a discharge rate of 0.1C. The first-cycle coulombic efficiency was calculated using the formula: First-cycle coulombic efficiency = First-cycle charge capacity at 2.0V / First-cycle lithium insertion capacity × 100%. Test data for the first-cycle coulombic efficiency and capacity retention after 600 cycles are shown in Table 1.
[0089] Example 2
[0090] This embodiment provides a preparation process of silicon-carbon negative electrode material based on liquid phase in-situ polymerization coating. The difference from Example 1 is that the mass ratio of starch to silicon-carbon composite precursor in step (3) is different, which is 1:1. The other preparation steps are the same as Example 1.
[0091] The specific surface area of the silicon-carbon negative electrode material prepared in this embodiment was tested using a specific surface area analyzer (model: Micromeritics ASAP2460). The test data are detailed in Table 1.
[0092] The silicon-carbon negative electrode material prepared in this example was used to prepare electrode pieces and assembled into button-type half-cells for testing. The button-type half-cell assembly and testing process were the same as in Example 1. The test data are detailed in Table 1.
[0093] Example 3
[0094] This embodiment provides a preparation process of silicon-carbon negative electrode material based on liquid phase in-situ polymerization coating. The difference from Example 1 is that the mass ratio of starch to silicon-carbon composite precursor in step (3) is different, which is 2:1. The other preparation steps are the same as Example 1.
[0095] The specific surface area of the silicon-carbon negative electrode material prepared in this embodiment was tested using a specific surface area analyzer (model: Micromeritics ASAP2460). The test data are detailed in Table 1.
[0096] The silicon-carbon negative electrode material prepared in this example was used to prepare electrode pieces and assembled into button-type half-cells for testing. The button-type half-cell assembly and testing process were the same as in Example 1. The test data are detailed in Table 1.
[0097] Example 4
[0098] This embodiment provides a preparation process of a silicon-carbon negative electrode material based on liquid phase in-situ polymerization coating. The difference from Example 1 is that the temperature of the hydrothermal reaction in step (3) is different, specifically 100°C. The other preparation steps are the same as those in Example 1.
[0099] The specific surface area of the silicon-carbon negative electrode material prepared in this embodiment was tested using a specific surface area analyzer (model: Micromeritics ASAP2460). The test data are detailed in Table 1.
[0100] The silicon-carbon negative electrode material prepared in this example was used to prepare electrode pieces and assembled into button-type half-cells for testing. The button-type half-cell assembly and testing process were the same as in Example 1. The test data are detailed in Table 1.
[0101] Example 5
[0102] This embodiment provides a preparation process of a silicon-carbon negative electrode material coated by liquid-phase in-situ polymerization. The difference from Example 1 is that in step (1), polyethylene glycol is used as the solvent; in step (3), phenol is used as the organic carbon source, and the temperature is 100°C; the other preparation steps are the same as those in Example 1.
[0103] The specific surface area of the silicon-carbon negative electrode material prepared in this embodiment was tested using a specific surface area analyzer (model: Micromeritics ASAP2460). The test data are detailed in Table 1.
[0104] The silicon-carbon negative electrode material prepared in this example was used to prepare electrode pieces and assembled into button-type half-cells for testing. The button-type half-cell assembly and testing process were the same as in Example 1. The test data are detailed in Table 1.
[0105] In order to better illustrate the effects of the embodiments of the present invention, a comparative example is compared with the above embodiments.
[0106] Comparative Example 1
[0107] This comparative example 1 provides a preparation process of a silicon-carbon negative electrode material, which is different from Example 1 in that gas-phase carbon coating is used. The specific process is: 100 g of the silicon-carbon composite precursor used in Example 1 is weighed, placed in a vapor deposition furnace, and heated to 600°C at a heating rate of 2°C / min under a nitrogen atmosphere. Acetylene gas is introduced at a gas flow rate of 10 L / min, and the mixture is kept warm for 5 hours. After cooling to room temperature, the material is sieved through a 300-mesh sieve to obtain a silicon-carbon negative electrode material.
[0108] The specific surface area of the silicon-carbon negative electrode material prepared in this comparative example was tested using a specific surface area analyzer (model: Micromeritics ASAP2460). The test data are detailed in Table 1.
[0109] The silicon-carbon negative electrode material prepared in this comparative example was used to prepare electrode pieces and assembled into button-type half-cells for testing. The button-type half-cell assembly and testing process were the same as in Example 1. The test data are detailed in Table 1.
[0110] Comparative Example 2
[0111] This comparative example 1 provides a preparation process of a silicon-carbon negative electrode material, which is different from that of Example 1 in that the mass ratio of starch to silicon-carbon composite precursor in step (3) is different, namely 0.1:1, and the other preparation steps are the same as those of Example 1.
[0112] The specific surface area of the silicon-carbon negative electrode material prepared in this comparative example was tested using a specific surface area analyzer (model: Micromeritics ASAP2460). The test data are detailed in Table 1.
[0113] The silicon-carbon negative electrode material prepared in this comparative example was used to prepare electrode pieces and assembled into button-type half-cells for testing. The button-type half-cell assembly and testing process were the same as in Example 1. The test data are detailed in Table 1.
[0114] Table 1 is a summary of the test data of Examples 1-5 and Comparative Examples 1-2: By comparing Comparative Example 1 with Examples 1-5, the effects of liquid phase in situ polymerization coating and traditional gas phase coating on material properties are compared; by comparing Comparative Example 2 with Examples 1-3, the effects of the amount of organic carbon source used on material properties are compared.
[0115]
[0116]
[0117] Table 1
[0118] From the comparison of the test data in Table 1, it can be seen that: Example 1, Example 2 and Example 3, as well as Comparative Example 2, are comparisons of increasing the amount of organic carbon source in the hydrothermal reaction process. As the amount of carbon source increases, the silicon-carbon precursor ratio decreases significantly. When the amount of carbon source and precursor reaches 1:1, the negative electrode material ratio tends to be stable and maintains 2m 2 / g or so.
[0119] The first-week coulombic efficiency and cycle performance of the silicon-carbon negative electrode materials after liquid-phase in-situ polymerization coating in Examples 1-5 were significantly improved compared to Comparative Example 1 (gas-phase coating). This is attributed to the fact that liquid-phase in-situ polymerization can form a uniform and dense carbon layer on the surface of the silicon-carbon negative electrode, which can improve the structural stability of the material and reduce the side reactions between the negative electrode and the electrolyte, thereby effectively inhibiting the generation of gas inside the battery and inhibiting the cumulative growth of the SEI film. In addition, the high-strength carbon layer of the silicon-carbon negative electrode material prepared in the embodiment of the present invention can exhibit better mechanical strength at high compaction density, inhibit expansion, reduce the risk of pulverization, and improve cycle stability.
[0120] Furthermore, Example 4 lowered the liquid phase coating temperature compared to Example 2. It can be observed that the coating effect is not much different at a liquid phase temperature of 100°C compared to 240°C. However, Example 4 shows improved first-cycle coulombic efficiency and cycling performance compared to Example 2. This is because the low-temperature liquid phase coating reduces the degree of oxidation in the sample, reducing side reactions between the negative electrode and the electrolyte.
[0121] Compared with Example 2, Example 5 uses a weakly oxidizing solvent for liquid-phase coating, and the coating temperature is lower, so the first-week coulombic efficiency and cycle performance are more excellent, and the performance of the material of Comparative Example 1 with gas-phase coating is also better.
[0122] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a silicon-carbon negative electrode material based on liquid phase in-situ polymerization coating, characterized in that: The preparation method comprises: Step S1, weighing a silicon-carbon composite precursor or preparing a silicon-carbon composite precursor; Step S2, mixing the silicon-carbon composite precursor and a solvent in a certain mass ratio, stirring evenly, to form a solvent system; Step S3, adding an organic carbon source to the solvent system and stirring uniformly to form an organic precursor solution; Step S4, subjecting the organic precursor solution to a hydrothermal reaction, causing the organic carbon source to undergo an in-situ polymerization reaction on the surface of the silicon-carbon composite precursor to form a dense coating layer, thereby obtaining an intermediate product; Step S5: heat-treating the intermediate product, sieving the discharged product, and obtaining a silicon-carbon negative electrode material coated by liquid phase in-situ polymerization.
2. The preparation method according to claim 1, characterized in that The preparation of the silicon-carbon composite precursor specifically includes: placing a porous carbon substrate in a deposition device, heating the substrate to 500° C. to 700° C. at a heating rate of 1° C. / min to 5° C. / min under a protective atmosphere, introducing a silicon source gas, and maintaining the temperature for 1 to 5 hours, so that silicon elements decomposed from the silicon source gas are deposited in the pores of the porous carbon substrate and grow into nano-silicon materials, thereby obtaining a silicon-carbon composite precursor; The porous carbon matrix comprises: one or more of resin carbon, biomass carbon, pitch coke or petroleum coke; The silicon source gas includes one or more of monosilane, disilane, dichlorosilane, trichlorosilane, tetrachlorosilane, and hexachlorodisilane; the flow rate of the silicon source gas is 1 L / min to 100 L / min; The protective gas of the protective atmosphere includes: nitrogen and / or argon; the flow rate of the protective gas is 1L / min to 50L / min; The specific surface area of the silicon-carbon composite precursor is 60 m 2 / g~200m 2 / g, and the carbon content in the silicon-carbon composite precursor is 40wt% to 55wt%.
3. The preparation method according to claim 1, characterized in that The solvent includes: deionized water or an organic solvent; the organic solvent includes: one or more of molecular alcohol solvents, ether solvents, amine solvents, and ester solvents; The mass ratio of the silicon-carbon composite precursor to the solvent is 0.3:10 to 3:10; The organic carbon source includes one or more of aromatic organic compounds, small molecule sugar organic compounds, polysaccharide organic compounds, organic acid organic compounds, and amide organic compounds; The mass ratio of the organic carbon source to the silicon-carbon composite precursor is 0.5:1 to 3:
1.
4. The preparation method according to claim 3, characterized in that The organic solvent specifically includes: one or more of ethylene glycol, isopropyl alcohol, polyethylene glycol, dimethyl ether, ethanolamine, methylethanolamine, methyl propionate, γ-butyrolactone, and tetrahydrofuran; The organic carbon source specifically includes: one or more of phenol, hydroquinone, catechol, starch, cyclodextrin, glucose, tannic acid, tartaric acid, and urea.
5. The preparation method according to claim 1, characterized in that The step S4 specifically includes: placing the organic precursor solution in a hydrothermal reactor, continuing to stir, heating to 25°C to 300°C under a pressure of 2Mpa to 3Mpa for a hydrothermal reaction, and keeping the temperature for 5 hours to 12 hours, so that the organic carbon source undergoes an in-situ polymerization reaction on the surface of the silicon-carbon composite precursor to form a dense coating layer, thereby obtaining an intermediate product.
6. The preparation method according to claim 1, characterized in that The step S5 specifically includes: placing the intermediate product in a high-temperature device, heating it to 400°C to 800°C under an inert gas environment for heat treatment for 2 hours to 5 hours, cooling it to room temperature, discharging it, and sieving it to obtain a silicon-carbon negative electrode material coated based on liquid phase in-situ polymerization.
7. A silicon-carbon negative electrode material based on liquid phase in-situ polymerization coating prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The silicon-carbon negative electrode material comprises: a silicon-carbon composite precursor, and a coating layer coated on the outer surface of the silicon-carbon composite precursor; The silicon-carbon composite precursor comprises: a porous carbon matrix, and nano-silicon materials deposited and grown in the pores and on the surface of the porous carbon matrix; The coating layer is a continuous film-like carbon coating layer formed by closely arranged carbon particles.
8. The silicon-carbon negative electrode material according to claim 7, characterized in that The specific surface area of the silicon-carbon composite precursor is 60 m 2 / g~200m 2 / g, and the carbon content in the silicon-carbon composite precursor is 40wt% to 55wt%.
9. A negative electrode plate, characterized in that: The negative electrode plate includes a silicon-carbon negative electrode material coated based on liquid phase in-situ polymerization prepared by the preparation method described in any one of claims 1-6, or a silicon-carbon negative electrode material coated based on liquid phase in-situ polymerization described in any one of claims 7-8.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the negative electrode sheet according to claim 9.
Citation Information
Cited By
Preparation method of solid-state battery silicon-based composite negative electrode material
CN121709569A
Raw material composition of positive electrode material, positive electrode material, preparation method thereof, electrode sheet and battery
CN122436492A